2016
DOI: 10.1117/1.jnp.10.033008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silver-nanoparticle layer in a chiral sculptured thin film for surface-multiplasmonic sensing of analytes in aqueous solution

Abstract: Multiple surface-plasmon-polariton (SPP) waves at a single free-space wavelength can be guided by the interface of a metal and a chiral sculptured thin film (STF). Multilayers comprising a chiral STF of lanthanum fluoride deposited on an aluminum thin film deposited on a glass substrate were fabricated. In some chips, a 5-nm-thick layer of silver nanoparticles was deposited at one of two selected depths in the chiral STF. The chips were then deployed in a prism-coupled configuration in a custom-built machine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The chiral material exhibits optical rotation phenomena and supports right circular polarization (RCP) and Left circular polarization (LCP) wave propagation, which means that the Transverse Magnetic (TM) and Transverse Electric (TE) modes cannot be studied independently, which is clear from the constitutive relationships i.e., D = ε E − jξ B and H = − jξ E + B / μ 24,25 . The following phasors that qualify all the characteristics of chiral material are given below; the E z and H z fields components in chiral components can be express as the superposition of the two given modes 28 where and are solutions to the wave equation that satisfy the wave equation when …”
Section: Formulations and Methodologymentioning
confidence: 99%
“…The chiral material exhibits optical rotation phenomena and supports right circular polarization (RCP) and Left circular polarization (LCP) wave propagation, which means that the Transverse Magnetic (TM) and Transverse Electric (TE) modes cannot be studied independently, which is clear from the constitutive relationships i.e., D = ε E − jξ B and H = − jξ E + B / μ 24,25 . The following phasors that qualify all the characteristics of chiral material are given below; the E z and H z fields components in chiral components can be express as the superposition of the two given modes 28 where and are solutions to the wave equation that satisfy the wave equation when …”
Section: Formulations and Methodologymentioning
confidence: 99%
“…Noting that most applications for biosensors involve small concentrations of analytes dispersed in solvents of refractive index close to that of water (n water = 1.333), we chose to calculate various R and R for n inf ∈ [1.3, 1.4] for equal increments ∆n inf = 0.0111 and ∆n inf ≈ 0.000503, respectively, as determined by J. All R and R were calculated for φ ∈ [−25 • , 24.8 • ] in steps of ∆φ = 0.2 • , which can be related [31] to θ by the standard law of refraction, yielding θ = 45 • + sin −1 n −1 prism sin φ for the prism with a 45 • -90 • -45 • triangle as its cross section. All data were computed using Mathematica R running on a laptop computer with a 4-core 2.4-GHz processor and 16 GB of RAM.…”
Section: Training Datamentioning
confidence: 99%
“…SPP-wave modes are capable of being excited by incident light of an arbitrary polarization state in the prism-coupled configuration when a periodically nonhomogeneous dielectric material is partnering a metal thin film [20]. However, experiments have shown that using p-polarized incident light results in a higher sensitivity over s-polarized incident light, based on the definition [31]…”
Section: Training With Incident Light Of Diverse Polarization Statesmentioning
confidence: 99%
See 2 more Smart Citations